A Feasibility Study of A Home-Based Program to Promote Perceived Adequate Milk - K Wood, Natsuko; M Lewis, Frances (Journal of Women's Reproductive Health, 2019)
Objective The purpose of this study was to evaluate the feasibility of a home-based educational skill building program to support exclusive breastfeeding for mothers in the early postpartum period. Specific aims were to: (1) evaluate the effectiveness of the study’s recruitment strategy, comparing the use of an intermediary with a direct approach, (2) examine intervention fidelity, (3) examine program adherence, and (4) assess the acceptability of the intervention to participants. Design and Sample A mixed methods within-group, three-occasion descriptive design, delivered to 14 dyads of breastfeeding mothers and their full-term singleton infants. Intervention The program was implemented during three, 60-90 minute educational training sessions in the home, delivered at 6, 13, and 27 days postpartum. Results Mothers who adhered to the intervention protocol correctly attributed their infant’s crying behavior to factors other than the adequacy of the mother’s milk supply. All participants were recruited through direct approach. The program was delivered as planned with high fidelity, a high retention rate, and with a high rate of acceptability. Conclusions A fully scripted, at-home, nurse-delivered educational skill building program can be delivered with efficiency to breastfeeding mothers with full-term singleton infants; intervention fidelity, retention, and acceptability were high.
Keywords: feasibility study; perceived insufficient milk; breast feeding; breastfeeding educational counseling; feeding behavior; health promotion.